2011
DOI: 10.1177/1934578x1100600320
|View full text |Cite
|
Sign up to set email alerts
|

Essential Oil of Plectranthus tenuicaulis Leaves from Gabon, Source of (R),(E)-6,7-Epoxyocimene. An Unusual Chemical Composition within the Genus Plectranthus

Abstract: Water distilled essential oils from leaves of Plectranthus tenuicaulis (Hook. f.) J. K. Morton collected in Gabon were analyzed using GC-FID and GC-MS. The main constituent, unusual within the genus Plectranthus, was isolated and formally identified as being the (+)-(R)enantiomer of (E)-6,7-epoxyocimene [(E)-myroxide]. This enantiomer, which represents about 75% of the essential oil, has been previously identified as a pheromone emitted by the male fruit-spotting bug Amblypelta nitida; this insect is responsib… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
6
0
1

Year Published

2012
2012
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(7 citation statements)
references
References 39 publications
0
6
0
1
Order By: Relevance
“…The EOs were analyzed by gas chromatography and gas chromatography coupled to mass spectrometry as described by Agnaniet et al [ 45 ].…”
Section: Methodsmentioning
confidence: 99%
“…The EOs were analyzed by gas chromatography and gas chromatography coupled to mass spectrometry as described by Agnaniet et al [ 45 ].…”
Section: Methodsmentioning
confidence: 99%
“…Plectranthus species have been used in folk medicine for treating skin, digestive and respiratory diseases [8,9]. Phytochemical studies on Plectranthus species showed the presence of many compounds belonging mainly to the groups of eudesmane sesquiterpenes, labdane, abietane, and ent-kaurane diterpenoids, triterpenoids [10][11][12] and essential oils with monoterpene hydrocarbons, oxygenated monoterpenes and sesquiterpene hydrocarbons as the main components [13][14][15][16][17][18]. P. cylindraceusHoechst.ex.…”
mentioning
confidence: 99%
“…P. tenuicaulis leaves were collected in Mopia (South-eastern Gabon) and analyzed using Gas Chomatography (GC-FID), Gas Chromatography-Mass Spectrometry (GC-MS), 1 H and 13 C NMR (Agnaniet et al, 2011;Agrebi et al, 2012).…”
Section: Methodsmentioning
confidence: 99%
“…Despite the many papers that have been published on the chemistry of Plectranthus (Abdel-Mogib et al, 2002) before our works (Agnaniet et al, 2011;Agrebi et al, 2012), to our knowledge, there are no previous reports on either the biological or chemical activities of the volatile (or non-volatile) compounds of P. tenuicaulis (Hook).…”
Section: Introductionmentioning
confidence: 94%